TAX MINIMIZATION MODERATING DETERMINANT TRANSFER PRICING IN ENERGY SECTOR COMPANIES INDONESIA - Rizky Dwi Kemal; Kustiyani, Siska Aura; Cahyani, Rahayu Nur; Hakim, Mohamad Zulman; Zulaecha, Hesty Erviani; Rachmania, Dewi (ZILLZELL MEDIA PRIMA, 2025)
The objective of this study is to examine and compare the various factors that influence transfer pricing decisions, with a particular emphasis on bonus schemes and loan contracts. It further explores the impact of tax reduction strategies on these factors within energy sector firms listed on the Indonesia Stock Exchange (IDX) between 2017 and 2023. The study's sample, consisting of 83 energy sector companies listed on the IDX, was selected using purposive sampling. Based on specific criteria, 49 data points and 7 energy-related firms were chosen as representatives for the analysis. The primary analytical technique applied in this study is moderated regression analysis. The findings indicate that transfer pricing strategies are significantly influenced by loan agreements and compensation schemes. However, tunneling incentives appear to have no substantial impact on transfer pricing decisions. Additionally, the moderating effect of tax minimization strengthens the relationship between loan agreements and transfer pricing. On the other hand, tax minimization seems to have minimal effect on the connection between transfer pricing, bonus plans, and tunneling incentives.